On Folnernets, Szego's theorem and other Eigenvalue distribution theorems - Bedos Erik (Oslo Oslo University. Institute of Mathematics, 1996)
510.7 Os82
Keywords: Eigenvalue distribution theorem; Folnernets; Szego's theorem